Composition for polyethylene foamed beads as well as preparation method and application of composition
By using a metallocene catalyst to prepare polyethylene A and B copolymers, combined with a batch impregnation foaming method, the problems of uneven cell structure and brittleness of polyethylene foam beads were solved, achieving high flexibility and excellent tensile strength, thus expanding the application range.
Patent Information
- Application Number
- CN202310824168.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-07-06
AI Technical Summary
Existing polyethylene foam beads suffer from problems such as uneven cell size, high pore breakage rate, high brittleness, and insufficient flexibility, which limit their application range.
Polyethylene A and polyethylene B copolymers prepared using metallocene catalysts, combined with antioxidants and other additives, were used to prepare polyethylene foam beads via a batch impregnation foaming method. The thickness of the lamellar crystals and the melt viscosity were controlled to obtain a uniform cell structure.
The prepared polyethylene foam beads are uniform in size, flexible, and have excellent tensile strength, making them suitable for cushioning components and low-temperature packaging, and exhibiting good foaming performance.
Smart Images

Figure BDA0004324474090000021 
Figure BDA0004324474090000091 
Figure BDA0004324474090000092
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastic packaging materials, and in particular relates to a composition for polyethylene foam beads and a preparation method and application thereof. Background Art
[0002] Polyethylene foam beads (EPE for short) are polyethylene pre-foamed particles prepared with physical foaming agents, and then various special-shaped complex products that meet design requirements are obtained through compression molding devices. EPE is mainly used in high-end mattresses, household items, and special application areas that require low temperatures, such as seafood refrigeration and packaging, insulation layers for circuits in low-temperature equipment, and insulation for precision instruments in aerospace and aircraft. Polyethylene foam products are more environmentally friendly and recyclable than polystyrene foam materials.
[0003] The physical foaming process of polyethylene foam beads in forming products is a physical foaming process. Compared with the traditional cross-linked chemical foaming method, it has the advantages of good hygienic performance, recyclability, and green environmental protection. Polyethylene foam beads are generally prepared by an intermittent foaming method. The specific process is to introduce a physical foaming agent near the molten state of polyethylene microparticles. When the foaming agent inside the polyethylene resin reaches saturation, the pressure is quickly released, and the polyethylene foam beads are obtained by using the instantaneous huge pressure and temperature changes. This type of production technology has certain difficulties in process operation control, and at the same time has high requirements on the physical properties and foaming characteristics of polyethylene resin. At present, the three different structures of polyethylene, LDPE, LLDPE and HDPE, all have certain deficiencies when used for foaming. Due to the presence of a large number of long and short chain branches in LDPE, the structure of the long chain branches can ensure a higher melt strength, which makes it difficult for the pore structure to collapse during foaming, but the physical and mechanical properties of a single LDPE foaming material are insufficient, which limits its application range. LLDPE has only a large number of short chain branches and a very small number of long chain branches, so the foaming ratio is not high during foaming, and the foam cells are easily broken, and the physical and mechanical properties are also insufficient. HDPE has fewer branches in its molecular chain structure, and usually has a high degree of crystallinity and a high melting temperature. Therefore, the required foaming temperature is high, the foaming temperature range is narrow, and the foaming ratio is low, making it difficult to foam.
[0004] The existing technology has the problems of uneven pores of the foamed beads, high pore breakage rate, high brittleness, insufficient flexibility, and resulting in poor product performance. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a composition for polyethylene foam beads, which has a reasonable raw material combination and is scientific and feasible.
[0006] The invention also provides a preparation method thereof, which is simple and feasible and suitable for mass production.
[0007] The present invention also provides applications thereof.
[0008] The composition for polyethylene foam beads of the present invention comprises the following raw materials of mass components:
[0009]
[0010] The polyethylene A is prepared by metallocene catalyst and is a copolymer of ethylene and comonomer α-olefin. The melt mass flow rate of the polyethylene A is 0.2-2.5 g / 10 min under the conditions of test temperature 190° C. and load 2.16 kg, and the density is 0.910-0.925 g / cm 3 ; preferably F1306ZR (0.50g / 10min, 0.9160g / cm 3 ), F1306ZP (0.78g / 10min, 0.9147g / cm 3 ), F181ZU (1.0g / 10min, 0.9179g / cm 3 More preferably, the MFR of polyethylene A is 0.5 to 1.0 g / 10 min, and the density is 0.913 to 0.918 g / cm 3 Generally speaking, the higher the MFR of polyethylene, the better its fluidity during the extrusion granulation process. However, in the foaming stage of polyethylene particles, the pores in the molten state are easily broken by the expanding CO2 gas. At a lower MFR, polyethylene has a higher melt viscosity, which can support the growth of pores in the foaming stage, and the pore walls are not easily damaged.
[0011] The polyethylene B is prepared by a metallocene catalyst and is a copolymer of ethylene and a comonomer α-olefin. The melt mass flow rate of the polyethylene B is 0.4-1.2 g / 10 min at a test temperature of 190° C. and a load of 2.16 kg, and the density is 0.930-0.942 g / cm 3 ; preferably QHM32F (0.63g / 10min, 0.9365g / cm 3 ), more preferably, the MFR of polyethylene B is 0.5 to 0.8 g / 10 min, and the density is 0.935 to 0.938 g / cm 3 .
[0012] The α-olefin is one or more of 1-butene, 1-hexene or 1-octene.
[0013] The weight average molecular weight of polyethylene A is 10.5×10 4 ~14.5×10 4 , the number average molecular weight is 3.0×10 4 ~4.5×10 4 , the weight average molecular weight of polyethylene B is 10.0×104 ~13.5×10 4 , the number average molecular weight is 2.5×10 4 ~4.3×10 4 . Tested using high temperature gel permeation chromatography (GPC) method.
[0014] The molar percentage of the comonomer of the polyethylene A is 2.60-3.60 mol% (tested by carbon nuclear magnetic resonance spectroscopy). Due to the use of a metallocene catalyst in production, the branching uniformity of the polyethylene molecular chain is better than that of LLDPE produced by a traditional Ziegler-Natta catalyst.
[0015] The relative content of polyethylene A lamellae with a thickness of 5 to 8 nm is ≥50%, preferably ≥55%, and more preferably ≥58%. The relative content of lamellae with a thickness of 9 to 12 nm is ≤26%, preferably ≤23%, and more preferably ≤20%. The thickness of the thickest lamellae is ≤12 nm, preferably ≤11 nm, and more preferably ≤10 nm. These structures are conducive to the control of process conditions during the foaming of polyethylene particles, and it is easy to obtain polyethylene foam beads with high foaming ratio and uniform pores.
[0016] The antioxidants are pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (1010), β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl (1076), 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (1330), 1,3,5-tris[[4-(1,1-dimethylethyl)-3-hydroxyphenyl] One or more of: [-2,6-dimethylphenyl]methyl]-1,3,5-triazine-2,4,6-trione (1790), tris(2,4-di-tert-butylphenyl) phosphite (168), bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite (626) or 3,9-dioctadecyloxy-2,4,8,10-tetraoxy-3,9-diphosphaspiro[5.5]undecane (618). An antioxidant is added to the polyethylene composition to ensure the long-term thermal oxygen stability, good appearance color and necessary durability of the polyethylene composition.
[0017] The other auxiliary agents include one or more of magnesium stearate, calcium stearate, zinc oxide, hydrated magnesium aluminate carbonate, hydrated magnesium silicate, glyceryl monostearate, polyethylene glycol or nano silicon dioxide.
[0018] The preparation method of the composition for polyethylene foam beads of the present invention comprises the following steps: weighing raw materials according to a proportion, placing them in a high-speed stirrer for uniform mixing, adding the uniformly mixed materials into a co-rotating twin-screw extruder for melt kneading, and pulling the wires after being melted by twin-screw extrusion, cooling the wires with cooling water, and then pelletizing the wires, adjusting the particle diameter to 0.1-0.5 mm and the particle length to 0.5-1.0 mm, so as to obtain the composition for polyethylene foam beads.
[0019] The highest section temperature of the twin-screw extruder is 140-180° C., the main engine speed of the extruder is 30-80 r / min, and the feeding speed is 10-30 r / min.
[0020] The composition for polyethylene foam beads of the present invention is used for preparing polyethylene foam beads by a kettle immersion foaming method.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The polyethylene composition obtained in the present invention is easy to prepare, and the obtained foamed beads are uniform in size, have good roundness, good foaming performance, good flexibility and excellent tensile strength. It can be used in the fields of cushioning components, packaging container interior materials and low-temperature packaging.
[0023] (2) The polyethylene B used in the present invention has a long-chain branch structure, which helps to improve the melt bonding stability.
[0024] (3) The polyethylene A and polyethylene B used in the present invention are produced using metallocene catalysts, so the branching uniformity of the polyethylene molecular chains is better than that of LLDPE produced using traditional Ziegler-Natta catalysts.
[0025] (4) The relative content of polyethylene A with a thickness of 5 to 8 nm in the polyethylene A used in the present invention is ≥50%, preferably ≥55%, and more preferably ≥58%. The relative content of polyethylene A with a thickness of 9 to 12 nm is ≤26%, preferably ≤23%, and more preferably ≤20%. The thickness of the thickest lamella is ≤12 nm, preferably ≤11 nm, and more preferably ≤10 nm. These structures are conducive to the control of process conditions during the foaming of polyethylene particles, and at the same time, it is easy to obtain polyethylene foam beads with a high foaming ratio and uniform pores.
[0026] (5) The polyethylene selected in the present invention has a lower MFR and a higher melt viscosity, which can support the growth of the cells during the foaming stage, and the cell walls are not easily damaged. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 : Relationship diagram between dynamic viscosity η' and imaginary viscosity η" of polyethylene B: QHM32F and comparative PE (cole-cole diagram);
[0028] Among them, the comparative PE in polyethylene B is QHM22F produced by Qilu Petrochemical, which has no long chain branching structure. The MFR of QHM22F is 0.7g / 10min under the test temperature of 190℃ and load of 2.16kg, and the density is 0.9379g / cm 3 . DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto.
[0030] Unless otherwise specified, all raw materials used in the examples are commercially available.
[0031] Unless otherwise indicated, implied from the context, or customary in the prior art, all parts and percentages in this application are based on weight, and the test and characterization methods used are all current as of the filing date of this application. Where applicable, the contents of any patent, patent application or publication referred to in this application are fully incorporated herein by reference, and their equivalent patent families are also incorporated by reference, especially the definitions of synthesis techniques, product and processing designs, polymers, comonomers, initiators or catalysts disclosed in these documents in the art. If the definition of a specific term disclosed in the prior art is inconsistent with any definition provided in this application, the definition of the term provided in this application shall prevail.
[0032] Numerical ranges in this application are approximate values, so unless otherwise stated, they may include numerical values outside the range. Numerical ranges include all numerical values from the lower limit to the upper limit increased by 1 unit, provided that there is an interval of at least 2 units between any lower value and any higher value. For example, if the recorded component, physical or other properties (such as molecular weight, melt index, etc.) are 100 to 1000, it means that all single values are clearly listed, such as 100, 101, 102, etc., and all sub-ranges, such as 100 to 166, 155 to 170, 198 to 200, etc. For a range comprising a numerical value less than 1 or comprising a fraction greater than 1 (such as 1.1, 1.5, etc.), 1 unit is appropriately regarded as 0.0001, 0.001, 0.01 or 0.1. For ranges containing single digit numbers less than 10 (eg, 1 to 5), typically one unit is considered to be 0.1. These are merely specific examples of what is intended, and all possible combinations of numerical values between the lowest value and the highest value enumerated are considered to be expressly stated in this application.
[0033] When used with respect to chemical compounds, unless expressly specified otherwise, the singular includes all isomeric forms and vice versa (e.g., "hexane" includes all isomers of hexane, individually or collectively). In addition, nouns using "a," "an," or "the" also include their plural forms unless expressly specified otherwise.
[0034] The terms "comprising", "including", "having" and their derivatives do not exclude the presence of any other components, steps or processes, and are irrelevant to whether these other components, steps or processes are disclosed in this application. To eliminate any doubt, unless explicitly stated, all compositions using the terms "comprising", "including", or "having" in this application may include any additional additives, adjuvants or compounds. On the contrary, except for those necessary for operating performance, the term "essentially consisting of..." excludes any other components, steps or processes from the scope of any description of the term below. The term "consisting of..." does not include any components, steps or processes that are not specifically described or listed. Unless explicitly stated, the term "or" refers to the listed individual members or any combination thereof.
[0035] The present invention is further described below in conjunction with embodiments, and the specific embodiments and testing methods are as follows:
[0036] Embodiment 1-2
[0037] Polyethylene A, F1306ZP: MFR is 0.78 g / 10 min at a test temperature of 190 °C and a load of 2.16 kg, and the density is 0.9147 g / cm 3 The molar percentage of the comonomer of polyethylene A is 3.48%, and the weight average molecular weight of polyethylene A is 13.3×10 4 , the number average molecular weight is 4.3×10 4 , the relative content of 5-8nm thick lamellae of polyethylene A is 55%, and the content of 9-12nm thick lamellae is 23%, and its two melting peak temperatures are 104°C and 118°C respectively;
[0038] Polyethylene B, QHM32F: MFR is 0.63 g / 10 min at a test temperature of 190 °C and a load of 2.16 kg, and the density is 0.9365 g / cm 3 , the melting peak temperature is 126°C, and the weight average molecular weight of polyethylene B is 10.8×10 4 , the number average molecular weight is 3.0×10 4 .
[0039] Embodiment 3-4
[0040] Polyethylene A, F1306ZR: MFR is 0.50g / 10min at a test temperature of 190°C and a load of 2.16kg, and the density is 0.9160g / cm 3 The molar percentage of the comonomer of polyethylene A is 3.52%, and the weight average molecular weight of polyethylene A is 13.9×10 4 , the number average molecular weight is 3.8×10 4 , the relative content of 5-8 nm thick lamellae of polyethylene A is 59%, the relative content of 9-12 nm thick lamellae is 25%, and the two melting peak temperatures are 103°C and 119°C respectively;
[0041] Polyethylene B, QHM32F: MFR is 0.63 g / 10 min at a test temperature of 190 °C and a load of 2.16 kg, and the density is 0.9365 g / cm 3 , the melting peak temperature is 126°C, and the weight average molecular weight of polyethylene B is 10.8×10 4 , the number average molecular weight is 3.0×10 4 .
[0042] Embodiment 5-6
[0043] Polyethylene A, F181ZU: MFR is 1.0g / 10min at a test temperature of 190°C and a load of 2.16kg, and the density is 0.9179g / cm 3 The molar percentage of the comonomer of polyethylene A is 2.70%, and the weight average molecular weight of polyethylene A is 14.5×10 4 , the number average molecular weight is 4.2×10 4 , the relative content of 5-8 nm thick lamellae of polyethylene A is 62%, the relative content of 9-12 nm thick lamellae is 25%, and the two melting peak temperatures are 106°C and 120°C respectively;
[0044] Polyethylene B, QHM32F: MFR is 0.63 g / 10 min at a test temperature of 190 °C and a load of 2.16 kg, and the density is 0.9365 g / cm 3 , the melting peak temperature is 126°C, and the weight average molecular weight of polyethylene B is 10.8×10 4 , the number average molecular weight is 3.0×10 4 .
[0045] Examples 1 to 6 Preparation of polyethylene composition microparticles
[0046] Weigh polyethylene A and B, antioxidant and other additives according to the proportion. The antioxidant described in the present invention is a mixture of main antioxidant 1010 and auxiliary antioxidant 168 in a mass ratio of 1:2, such as commercially available B215, or similar products can be implemented. Other additives are a mixture of calcium stearate, glyceryl monostearate and nano-silicon dioxide in a mass ratio of 1:1:2, wherein calcium stearate, glyceryl monostearate and nano-silicon dioxide are all commercially available products. Place them in a high-speed mixer and mix them evenly at a speed of 1500r / min and a stirring time of 3min. Add the evenly mixed materials into a co-rotating twin-screw extruder for melt mixing. The twin-screw extruder has a diameter of 16mm and an aspect ratio of 25:1. The highest section temperature of the extruder is 180°C, the main engine speed of the extruder is 50r / min, and the feeding speed is 20r / min. The polyethylene material was melted by twin-screw extrusion and then drawn into a wire and cooled by cooling water before being cut into pellets. The particle length was adjusted to a particle diameter of 0.3 mm and a particle length of 0.5 mm to obtain polyethylene microparticles with an average particle mass of 1.6 mg.
[0047] Preparation of Examples 1 to 6 Polyethylene Foam Beads:
[0048] The polyethylene foam beads were prepared by a kettle immersion foaming method. The prepared polyethylene particles were placed in a temperature and pressure resistant reactor and dispersed in an aqueous dispersion medium. Supercritical carbon dioxide was introduced as a foaming agent, and the air in the reactor was evacuated. The temperature was controlled to be 117.5±12.5°C and the pressure was 3.5±1.5MPa. After the holding time was 25 minutes, the discharge port was opened to release the material into a collector to obtain polyethylene foam beads with a foaming ratio of 20±5 times.
[0049] The types and mixing ratios of polyethylene 1 and polyethylene 2 in Comparative Examples 1 to 6 are as follows:
[0050] Comparative Examples 1-2
[0051] Polyethylene 1: mLLDPE1, MFR is 0.81 g / 10 min at a test temperature of 190 °C and a load of 2.16 kg, and the density is 0.9154 g / cm 3 , the relative content of 5-8nm thick platelets is 34%, the content of 9-12nm thick platelets is 50%, the melting peak temperatures are 101°C and 119°C respectively, mLLDPE1 is XP8784, produced by ExxonMobil;
[0052] Polyethylene 2: Polyethylene B, QHM32F: MFR is 0.63g / 10min at a test temperature of 190°C and a load of 2.16kg, and the density is 0.9365g / cm 3 , melting peak temperature 126℃.
[0053] Comparative Examples 3-4
[0054] Polyethylene 1: LDPE1, MFR is 0.30g / 10min at a test temperature of 190°C and a load of 2.16kg, and the density is 0.920g / cm 3 , the melting peak temperature is 107℃; LDPE1 is high-pressure polyethylene, brand 2100TN00, produced by Qilu Petrochemical.
[0055] Polyethylene 2: Polyethylene B, QHM32F: MFR is 0.63g / 10min at a test temperature of 190°C and a load of 2.16kg, and the density is 0.9365g / cm 3 , melting peak temperature 126℃.
[0056] Comparative Examples 5-6
[0057] Polyethylene 1: LLDPE1, MFR is 1.0g / 10min at a test temperature of 190°C and a load of 2.16kg, and the density is 0.919g / cm 3 , the melting peak temperature is 123℃; LLDPE1 is a linear low-density polyethylene produced by a titanium catalyst, with a grade of QLLP01, produced by Qilu Petrochemical;
[0058] Polyethylene 2: Polyethylene vs. PE, MFR is 0.7g / 10min at a test temperature of 190°C and a load of 2.16kg, and the density is 0.9379g / cm 3 , the melting peak temperature is 127°C. The polyethylene comparison PE is QHM22F produced by Qilu Petrochemical, which uses a different type of metallocene catalyst from QHM32F and has no long-chain branching structure.
[0059] The relationship diagram (cole-cole diagram) between the dynamic viscosity η' and the imaginary viscosity η" of polyethylene B:QHM32F and comparative PE tested by dynamic rheometer is shown in Figure 1 In the figure, the upward curve of polyethylene B: QHM32F indicates that it has a long chain branching structure, while the semicircular curve of the comparative resin PE does not rise, indicating that it has no long chain branching. Compared with the comparative PE without long chain branching, the long chain branching structure of polyethylene B is helpful for melt bonding stability.
[0060] The preparation method and steps of the comparative example are the same as those of Examples 1 to 6.
[0061] The proportions and performance test results of the polyethylene compositions of the embodiments and comparative examples are shown in Tables 1 to 4, respectively.
[0062] Table 1 Example
[0063]
[0064] Table 2 Comparative Examples
[0065]
[0066] Table 3 Physical properties of expanded beads of Examples 1-6
[0067]
[0068] Table 4 Physical properties of foamed beads of comparative examples 1-6
[0069]
[0070] The test method is as follows:
[0071] The melt flow rate (MFR) is tested according to GB / T 3682.1-2018;
[0072] Density is tested according to GB / T 1033.2-2010;
[0073] Tensile strength and elongation at break are tested according to GB / T 6344;
[0074] The uniformity of cell size was observed using a scanning electron microscope.
[0075] Melting temperature and crystallization heat fraction were tested by DSC.
[0076] Each embodiment in this specification is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0077] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A composition for polyethylene foam beads, characterized in that Raw materials including the following quality components: The polyethylene A is prepared by metallocene catalyst and is a copolymer of ethylene and comonomer α-olefin. The melt mass flow rate of the polyethylene A is 0.2-2.5 g / 10 min under the conditions of test temperature 190° C. and load 2.16 kg, and the density is 0.910-0.925 g / cm 3 ; The polyethylene B is prepared by a metallocene catalyst and is a copolymer of ethylene and a comonomer α-olefin. The melt mass flow rate of the polyethylene B is 0.4-1.2 g / 10 min at a test temperature of 190° C. and a load of 2.16 kg, and the density is 0.930-0.942 g / cm 3 .
2. The composition for polyethylene foam beads according to claim 1, characterized in that The α-olefin is one or more of 1-butene, 1-hexene or 1-octene.
3. The composition for polyethylene foam beads according to claim 1, characterized in that: The weight average molecular weight of polyethylene A is 10.5×10 4 ~14.5×10 4 , the number average molecular weight is 3.0×10 4 ~4.5×10 4 , the weight average molecular weight of polyethylene B is 10.0×10 4 ~13.5×10 4 , the number average molecular weight is 2.5×10 4 ~4.3×10 4 .
4. The composition for polyethylene foam beads according to claim 1, characterized in that: The molar percentage of the comonomer of the polyethylene A is 2.60-3.60 mol%.
5. The composition for polyethylene foam beads according to claim 1, characterized in that: The relative content of polyethylene A flakes with a thickness of 5 to 8 nm is ≥50%, the relative content of flakes with a thickness of 9 to 12 nm is ≤26%, and the thickness of the thickest flake is ≤12 nm.
6. The composition for polyethylene foam beads according to claim 1, characterized in that: The antioxidant is one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 1,3,5-tris[[4-(1,1-dimethylethyl)-3-hydroxy-2,6-dimethylphenyl]methyl]-1,3,5-triazine-2,4,6-trione, tris(2,4-di-tert-butylphenyl) phosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite or 3,9-dioctadecyloxy-2,4,8,10-tetraoxy-3,9-diphosphaspiro[5.5]undecane.
7. The composition for polyethylene foam beads according to claim 1, characterized in that: The other auxiliary agents include one or more of magnesium stearate, calcium stearate, zinc oxide, hydrated magnesium aluminate carbonate, hydrated magnesium silicate, glyceryl monostearate, polyethylene glycol or nano silicon dioxide.
8. A method for preparing the composition for polyethylene foam beads according to any one of claims 1 to 7, characterized in that: The raw materials are weighed in proportion and mixed evenly, and the evenly mixed materials are added to a co-rotating twin-screw extruder for melt mixing. After the materials are melted by twin-screw extrusion, the wire is pulled through cooling water for cooling and then pelletized. The particle diameter is adjusted to 0.1-0.5 mm and the particle length is 0.5-1.0 mm to obtain a composition for polyethylene foam beads.
9. The method for preparing the composition for polyethylene foam beads according to claim 8, characterized in that: The highest section temperature of the twin-screw extruder is 140-180° C., the main engine speed of the extruder is 30-80 r / min, and the feeding speed is 10-30 r / min.
10. Use of the composition for polyethylene foam beads according to any one of claims 1 to 7, characterized in that: Used for preparing polyethylene foam beads by kettle impregnation foaming method.
Citation Information
Patent Citations
Polyethylene composition, foamed bead and preparation method thereof, and foamed bead molding body
CN107312231A
Polyethylene composition, foamed bead and preparation method thereof, and foamed bead molding body
CN107312232A
Polyethylene resin composition, polyethylene resin granules, polyethylene foamed beads and preparation method and molded body thereof
CN111849055A
Process for producing foam beads using a modified ethylene-based polymer
IN202017010163A
Mold pack and its production
JP1999116718A